2009
DOI: 10.5194/acp-9-7461-2009
|View full text |Cite
|
Sign up to set email alerts
|

Detailed heterogeneous chemistry in an urban plume box model: reversible co-adsorption of O<sub>3</sub>, NO<sub>2</sub>, and H<sub>2</sub>O on soot coated with benzo[a]pyrene

Abstract: Abstract. This study assesses in detail the effects of heterogeneous chemistry on the particle surface and gas-phase composition by modeling the reversible co-adsorption of O 3 , NO 2 , and H 2 O on soot coated with benzo[a]pyrene (BaP) for an urban plume scenario over a period of five days. By coupling the Pöschl-Rudich-Ammann (PRA) kinetic framework for aerosols ) to a box model version of the gas phase mechanism RADM2, we are able to track individual concentrations of gas-phase and surface species over the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 79 publications
2
39
4
Order By: Relevance
“…Longer half-lives in response to higher water vapour concentrations in the atmosphere were also observed by Springmann et al (2009) and can be explained by the large fraction of active surface sites that is covered by H 2 O molecules and thus unavailable for chemical reactions. Hence, in the high RH scenarios, less PAH is oxidised per unit time.…”
Section: Population Pah Half-lifementioning
confidence: 95%
See 3 more Smart Citations
“…Longer half-lives in response to higher water vapour concentrations in the atmosphere were also observed by Springmann et al (2009) and can be explained by the large fraction of active surface sites that is covered by H 2 O molecules and thus unavailable for chemical reactions. Hence, in the high RH scenarios, less PAH is oxidised per unit time.…”
Section: Population Pah Half-lifementioning
confidence: 95%
“…Absolute values, however, differ quite strongly because Shiraiwa et al (2009) did not consider changes in gas phase composition, while Springmann et al (2009) simulated fewer heterogeneous reactions and used different values for some of the physico-chemical parameters.…”
Section: Individual Particlesmentioning
confidence: 99%
See 2 more Smart Citations
“…Using K2-SURF Shiraiwa et al (2011b) showed that long-lived reactive oxygen intermediates are formed in the reaction of ozone with aerosol particles. Springmann et al (2009) and Kaiser et al (2011) demonstrated the applicability and usefulness of the PRA framework in an urban plume box model of the degradation of benzo [a]pyrene on soot by ozone and nitrogen dioxide. Pfrang et al (2010) developed a kinetic double-layer model coupling aerosol surface and bulk chemistry (K2-SUB), in which mass transport and chemical reactions in the bulk are not explicitly resolved but represented by a reacto-diffusive flux analogous to traditional resistormodel formulations.…”
mentioning
confidence: 99%